Religiosity and Risky Behavior - seyed alireza afshani; shermin emami; akram mirmongereh (توسعه اجتماعی)
The current study has been conducted to determine the relationship between religiosityand risky behaviors among students at Yazd University. Theoretical frameworks derived from the theories of Kent, Webber, Wach, Le Vantal and Cults, Gluck and Stark and have been carried out through descriptive and cross-sectional and navigational methods. The data was collected through stratified sampling from 320 students (160 male–160 female) who were enrolled at the University of Yazd and was analyzed with SPSS and Lisrel. The measurement tool of risky behavior is Iranian Youth risk scale. The data was analyzed using structural equation modeling, correlation and t-test. The results indicated that risky behavior (overall index) among men and women such as drugs, alcohol, smoking, violence, sexual behavior, relationships with the opposite sex and dangerous driving was significant and also higher in men than women. Also, risky behavior (overall index) such as smoking and dangerous driving is significant among singles and married that is significantly higher in singles. The Pearson statistical exam also showed that there is a significant negative correlation between the degree of religiosity and riskybehavior. Structural equation modeling analysis results designated that the degree of religiosity torisky behaviors is -0.54 that shows the inverse relationship between the two variables. Therefore, and increase in religiosity reduces risky behavior. Generally, this study emphasizes the important role of religion in reducing risky behaviors.